Exploring Religious Change: The Baduy Tribe’s Perspective on Leaving Sunda Wiwitan for Islam - Fadliansyah, Fauzi; Maksum, Arifin; Nurhanasah, Nina (Talenta Publisher, 2025)
This research examines the religious transformation within the Original Baduy community, focusing on how individuals perceive and experience the shift from the traditional Sunda Wiwitan belief system to Islam. It explores the perspectives of both those who continue to uphold ancestral beliefs and those who have embraced Islam, aiming to understand how this transition is interpreted and negotiated within the cultural and social context of the Baduy people. Utilizing a qualitative research approach, the study involves in-depth interviews, observation, and document analysis. Triangulation of data from multiple sources and theoretical frameworks ensures the credibility and depth of findings. The analysis draws upon theories of religious conversion, identity formation, and cultural continuity to offer a comprehensive understanding of the transformation process. The findings indicate that the change in religious orientation does not cause significant conflict within the community. Instead, peaceful coexistence is maintained between followers of Sunda Wiwitan and Muslim Baduy members, rooted in shared kinship values, strong customary laws, and a deeply ingrained culture of tolerance. Religious conversion is often influenced by intermarriage, social interaction, exposure to Islamic teachings, and personal spiritual development. Importantly, cultural traditions such as rituals and community ceremonies continue to be upheld by both religious groups, reflecting a form of spiritual syncretism and mutual respect. The study highlights how the Baduy people manage religious plurality while preserving community unity and cultural identity. It contributes to broader discussions on indigenous religions, religious change, and interfaith harmony in traditional societies, offering valuable insights into how cultural resilience supports peaceful religious transitions.